2021
DOI: 10.21203/rs.3.rs-164276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Consumption-Based Carbon Emissions in Chile: Application of Non-Linear ARDL

Abstract: In recent years, a growing number of scholars have employed various proxies of environmental degradation to understand the reasons behind rising environmental degradation. However, very few studies consider consumption-based carbon emissions even though a clear understanding of the impact of consumption patterns is essential to redirecting the pattern to more sustainable consumption. Thus, this study takes a step forward by using consumption-based carbon emissions (CCO2) as a proxy of environmental degradation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Temporary changes in tiny sample data can be removed using the frequency domain. Furthermore, the frequency domain technique can distinguish between nonlinearity and causality levels and demonstrate causality between variables with various frequencies (Adebayo, Udembo, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Temporary changes in tiny sample data can be removed using the frequency domain. Furthermore, the frequency domain technique can distinguish between nonlinearity and causality levels and demonstrate causality between variables with various frequencies (Adebayo, Udembo, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The authors found that GDP positively influences CCO 2 . Using the NARDL, the study conducted on Chile by Adebayo et al [43] over the period from 1990 to 2018 found that both negative and positive variations in GDP contribute to CCO 2 in Chile. For Japan, the investigation of [44] using quarterly data ranging from 1990Q1-2015Q4 established the presence of a positive interconnectedness between CO 2 and GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Chile ratified the Paris Agreement of 2015 and started to take the necessary steps to mitigate GHG emissions at a national level. Renewable energy investments have also been increased recently, and it seems that Chile is one of the few countries that is likely to meet its emission reduction targets (Adebayo et al, 2021; Benavente, 2016; Cansino et al, 2018; Simsek et al, 2020). Chile is also an emerging market engaging in international trade, which fits into our research as a good example.…”
Section: Introductionmentioning
confidence: 99%